Single Fluorescence Channel-based Multiplex Detection of Avian Influenza Virus by Quantitative PCR with Intercalating Dye - Ahberg, Christian D. (Sci Rep, 2015)
Since its invention in 1985 the polymerase chain reaction (PCR) has become a well-established method for amplification and detection of segments of double-stranded DNA. Incorporation of fluorogenic probe or DNA intercalating dyes (such as SYBR Green) into the PCR mixture allowed real-time reaction monitoring and extraction of quantitative information (qPCR). Probes with different excitation spectra enable multiplex qPCR of several DNA segments using multi-channel optical detection systems. Here we show multiplex qPCR using an economical EvaGreen-based system with single optical channel detection. Previously reported non quantitative multiplex real-time PCR techniques based on intercalating dyes were conducted once the PCR is completed by performing melting curve analysis (MCA). The technique presented in this paper is both qualitative and quantitative as it provides information about the presence of multiple DNA strands as well as the number of starting copies in the tested sample. Besides important internal control, multiplex qPCR also allows detecting concentrations of more than one DNA strand within the same sample. Detection of the avian influenza virus H7N9 by PCR is a well established method. Multiplex qPCR greatly enhances its specificity as it is capable of distinguishing both haemagglutinin (HA) and neuraminidase (NA) genes as well as their ratio.